Perlindungan Hak Konstitusional Pemohon Dalam Proses Pengujian Undang-Undang oleh Mahkamah Konstitusi Republik Indonesia - Sapanah, Mawar; Mufidah, Putri; Faridah, Shafa Fauziyyah Nur; Busroni, Rania Syifa (Media Hukum Indonesia (MHI), 2025)
The Constitutional Court of the Republic of Indonesia was established as an institution tasked with upholding the supremacy of the Constitution and protecting the constitutional rights of citizens. One of its primary authorities is the judicial review of legislation against the 1945 Constitution of the Republic of Indonesia. This article examines the procedural mechanisms of the Constitutional Court in safeguarding the constitutional rights of petitioners, and to what extent these procedures ensure the fulfillment of the right to justice. Utilizing a normative legal method, this study reveals that although the procedural law of the Court is designed to uphold the principles of fairness and accessibility, significant challenges remain in ensuring optimal protection for petitioners. While the Court’s decisions are final and binding, granting them strong legal force, their implementation and impact on legislative reform still require robust institutional support.